"Stand up, speak out and act": A critical reading of Australia's White Ribbon campaign. Issue 2 (June 2018) - Seymour, Kate
The White Ribbon campaign has come to occupy a central position in Australia's efforts to address violence against women. This article critically examines key elements of the White Ribbon awareness-raising campaigns, paying particular attention to the conceptualisation of gender, masculinity, and equality. It is argued that White Ribbon's reliance on a binary view of gender, together with its emphasis on the attitudes and acts of individual men, contributes to the obscuration of men's collective advantage. Acknowledging the intersectional positionings associated with hierarchies of power and privilege, this article calls for deeper engagement with the complexities of gender and violence; a commitment to both engage with and transcend the interpersonal.